Dual impact of elevated temperature on plant defence and bacterial virulence in Arabidopsis - Bethany Huot (Nature Portfolio, 2017)
Temperature is known to influence plant disease development. Here Huot et al. show that elevated temperature can enhance Pseudomonas syringae effector delivery into plant cells and suppress SA biosynthesis while also finding a temperature-sensitive branch of the SA signaling pathway in Arabidopsis.